Preparation method and application for constructing MOF (Metal Organic Framework) derivative electrode material by using PET (Polyethylene Terephthalate) waste plastics as organic ligand source

CN119640305APending Publication Date: 2025-03-18SUN YAT SEN UNIV

Patent Information

Application Number
CN202510124820.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-26
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

In the existing electrocatalytic CO2 reduction technology, the catalyst costs are high and the activity is low, and the preparation method of MOF electrode materials is complex and expensive.

Method used

By using PET waste plastic as the source of organic ligands, MOF materials were synthesized by one pot or two-step process path, and combined with materials such as Nafion to prepare MOF-derived electrode materials.

Benefits of technology

In the process of electrocatalytic CO2 reduction, MOF-derived electrode materials show good catalytic performance, and the Faraday efficiency of formic acid production reaches 53%. At the same time, PET waste plastic is effectively utilized, reducing environmental pollution.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119640305A_ABST
    Figure CN119640305A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method and application for constructing an MOF (Metal Organic Framework) derivative electrode material by using PET (Polyethylene Terephthalate) waste plastics as an organic ligand source. The method comprises the following steps: directly adopting PET waste plastics or a depolymerization product terephthalic acid thereof, combining with a metal salt and an organic solvent, reacting under a hydrothermal condition, and performing centrifugal separation, washing and drying after the reaction to obtain the MOF material. Furthermore, the MOF material is prepared into a corresponding electrode material, and the electrode material is successfully applied to the field of electrocatalytic CO2 reduction. The MOF electrode material prepared by PET derivation shows good catalytic performance in the process of electrocatalytic CO2 reduction by virtue of rich active sites and excellent electron transfer capability of the MOF electrode material. The preparation method is simple in process and low in cost, not only realizes effective recycling of the PET waste plastics, but also contributes to reduction of environmental pollution, and is an innovative technology with both environmental benefits and economic benefits.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of plastic chemical recycling and electrocatalytic reduction, and specifically relates to a preparation method and application of MOF-derived electrode materials using PET waste plastics as an organic ligand source. Background Art

[0002] Polyethylene terephthalate (PET) is widely used in production and life due to its excellent physical and chemical properties. However, due to the high stability of PET, it takes 300-500 years for it to be completely degraded in the natural environment. Waiting for natural degradation is almost impossible, and the treatment of PET waste plastics has become an urgent problem to be solved.

[0003] CO 2 As a major greenhouse gas, its excessive emission has led to serious problems such as global warming and ecosystem imbalance. 2 Reduction is the use of renewable electricity to convert CO 2 The technology of converting electrocatalytic CO into high value-added products does not pollute the environment and has economic potential. 2 There are problems such as high catalyst cost and low activity in the reduction process, and it is necessary to develop efficient catalysts to solve these problems.

[0004] MOF material is a porous three-dimensional structure formed by the coordination of metal ions or metal clusters and organic ligands. This material has a large specific surface area and excellent CO 2 Advantages such as adsorption capacity make MOF materials very popular in CO 2 It has unique advantages in the field of reduction. For example, patent CN202011079183.2 discloses a sulfur-modified Cu-based MOF material that exhibits excellent ethylene selectivity at a voltage of -1.30V. Another example is patent CN202110597920.6, which proposes a Cu-MOF material prepared by reacting 3,4,9,10-perylenetetracarboxylic dianhydride with 1-(3-aminopropyl)imidazole to generate PDI, which is then reacted with cupric chloride. Although MOF materials have rich pores and framework structures that promote the transport of reaction substrates and products, and in the electrocatalytic CO 2 It shows good catalytic efficiency in reduction, but the preparation of its electrode materials still faces problems such as complex methods and high costs. Summary of the invention

[0005] The purpose of the present invention is to provide a method for preparing a MOF-derived electrode material with strong catalytic performance by using PET waste plastics as an organic ligand source.

[0006] The above-mentioned object of the present invention is achieved by the following technical solutions:

[0007] A method for preparing a MOF-derived electrode material using PET waste plastic as a source of organic ligands comprises the following steps:

[0008] S1. Put PET waste plastic or terephthalic acid obtained by depolymerization of PET into a glass beaker, add metal salt, N,N-dimethylformamide, alcohol and deionized water, mix and stir, transfer to a polytetrafluoroethylene-lined reactor, and react at a certain temperature;

[0009] S2. After cooling, centrifugation, washing and drying are performed to obtain the MOF material;

[0010] S3. Take MOF material, add Nafion and alcohol to make ink-like slurry, and apply it on carbon paper after ultrasonic treatment to prepare MOF-derived electrode material.

[0011] Preferably, the metal salt in step S1 is one or more of manganese chloride, manganese nitrate, manganese sulfate, ferrous sulfate, ferrous nitrate, ferrous chloride, ferrous acetylacetonate, ferric sulfate, ferric nitrate, ferric chloride, copper nitrate, copper sulfate, copper chloride, copper bromide, copper acetylacetonate, ruthenium trichloride, ruthenium nitrate and hydrate.

[0012] Preferably, the alcohol in step S1 is one or more of methanol, ethanol, ethylene glycol, 1,3-propylene glycol, glycerol, 1,4-butanediol, and phenylethyl alcohol.

[0013] Preferably, in step S1, the molar ratio of the PET waste plastic to the metal salt is 0.5-3:1.

[0014] Preferably, in step S1, the volume ratio of N,N-dimethylformamide to alcohol and deionized water is 1-3:0-3:1.

[0015] Preferably, in step S1, the temperature is 80-180°C and the reaction time is 24-48h.

[0016] Preferably, in step S3, the solid-liquid ratio of the MOF material to Nafion is 0.1-1:1 g / mL.

[0017] The MOF-derived electrode materials have been shown to be effective in electrocatalytic CO 2 Application in reduction. Using the MOF-derived electrode material to electrocatalyze CO 2 The method for preparing formic acid by reduction comprises the following steps: using an electrochemical workstation, using the MOF-derived electrode material of claim 1 as a working electrode, an Ag / AgCl electrode as a reference electrode, and using CO 2 The saturated metal salt solution is used as the electrolyte, and the electrocatalytic CO 2The metal salt is one or more of potassium bicarbonate, potassium chloride, potassium sulfate, sodium sulfate, sodium bicarbonate, cesium bicarbonate, and cesium sulfate; the electrolyte concentration is 0.1-1.2 mol / L; the amount of MOF-derived electrode material loaded on carbon paper is 0.5-2.5 mg / cm 2 , the counter electrode is a platinum sheet.

[0018] Compared with the prior art, the present invention has the following beneficial effects:

[0019] The present invention adopts a one-pot or two-step process route to effectively use terephthalic acid obtained after PET depolymerization as an organic ligand to synthesize MOF materials. The MOF electrode material derived from PET has abundant active sites and excellent electron transfer ability in electrocatalytic CO 2 The reduction process showed good catalytic performance: at a potential of -1.65V (vs.Ag / AgCl), the Faradaic efficiency of formic acid generation reached 53%, which is a medium level in this field. This technology not only successfully converted PET waste plastics into high-value materials, but also effectively reduced environmental pollution and promoted the recycling of resources. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 XRD diagram of the MOF electrode material prepared in Examples 1-4.

[0021] Figure 2 This is the LSV diagram of the Cu-MOF electrode material prepared in Example 4.

[0022] Figure 3 This is the Faraday efficiency diagram of the Cu-MOF electrode material prepared in Example 4. DETAILED DESCRIPTION

[0023] In order to more clearly and completely describe the technical solution of the present invention, the present invention is further described in detail through specific embodiments below. It should be understood that the specific embodiments described herein are only used to explain the present invention, and are not used to limit the present invention. Various changes can be made within the scope of the rights of the present invention.

[0024] Example 1

[0025] A method for preparing a Fe-MOF catalyst using PET waste plastic as an organic ligand source comprises the following steps:

[0026] S1. Take 2.3 g PET, 3.34 g ferrous sulfate heptahydrate, 30 mL N,N-dimethylformamide, and 15 mL deionized water, mix and stir, transfer to a polytetrafluoroethylene-lined reactor, and place in an oven at 180°C for 24 h.

[0027] S2. After cooling, 2.1 g of Fe-MOF material was obtained through centrifugal separation, washing and drying.

[0028] S3. Take 10 mg of the Fe-MOF material, add 1 mL of ethanol and 100 μL of Nafion to make an ink-like slurry, and apply it on carbon paper after ultrasonication to prepare a Fe-MOF electrode material.

[0029] The XRD pattern of the prepared Fe-MOF electrode material is shown in Figure 1 As shown, the diffraction peaks at 8.8°, 9.2°, and 10° are the characteristic peaks of Fe-MOF, indicating the successful synthesis of Fe-MOF.

[0030] Example 2

[0031] A method for preparing a Mn-MOF catalyst using PET waste plastic as an organic ligand source comprises the following steps:

[0032] S1. Take 2 g PET, 1.51 g manganese chloride, 30 mL N,N-dimethylformamide, and 15 mL deionized water, mix and stir, transfer to a polytetrafluoroethylene-lined reactor, and place in an oven at 180 °C for 24 h.

[0033] S2. After cooling, 2.05 g of Mn-MOF material was obtained through centrifugal separation, washing and drying.

[0034] S3. Take 10 mg of the Mn-MOF material, add 1 mL of ethanol and 100 μL of Nafion to make an ink-like slurry, and apply it on carbon paper after ultrasonication to prepare a Mn-MOF electrode material.

[0035] The XRD pattern of the prepared Mn-MOF electrode material is shown in Figure 1 As shown, the characteristic peak appearing at 9.5° indicates the successful synthesis of Mn-MOF.

[0036] Example 3

[0037] A method for preparing a Ru-MOF catalyst using PET waste plastic as an organic ligand source comprises the following steps:

[0038] S1. Depolymerization of PET to obtain terephthalic acid: Add 10g of PET waste plastic into a 500mL round-bottom flask, add 12g of NaOH, 55mL of ethylene glycol, condense and reflux at 180℃ for 4h, then add 150mL of deionized water and stir evenly. Filter the mixture and add 5mol / L of H 2 SO 4 The solution was stirred for 30 minutes to obtain a white precipitate, which was then centrifuged to obtain a white product, which was then washed and dried to obtain terephthalic acid.

[0039] S2. Weigh 2 g of terephthalic acid obtained in step S1, 2.49 g of ruthenium chloride hydrate, 30 mL of N,N-dimethylformamide, and 15 mL of deionized water, mix well, transfer to a polytetrafluoroethylene-lined reactor, and place in an oven at 180°C for 24 h.

[0040] S3. After cooling, 0.36 g of Ru-MOF material was obtained through centrifugal separation, washing and drying.

[0041] S4. Take 10 mg of the Ru-MOF material, add 1 mL of ethanol and 100 μL of Nafion to make an ink-like slurry, and apply it on carbon paper after ultrasonication to prepare a Ru-MOF electrode material.

[0042] The XRD pattern of the prepared Ru-MOF electrode material is shown in Figure 1 As shown, the diffraction peak appearing at 9° indicates the successful synthesis of Ru-MOF.

[0043] Example 4

[0044] A method for preparing a Cu-MOF catalyst using PET waste plastic as an organic ligand source comprises the following steps:

[0045] S1. Depolymerization of PET to obtain terephthalic acid: Add 10g of PET waste plastic into a 500mL round-bottom flask, add 12g of NaOH, 55mL of ethylene glycol, condense and reflux at 180℃ for 4h, then add 150mL of deionized water and stir evenly. Filter the mixture and add 5mol / L of H 2 SO 4 The solution was stirred for 30 minutes to obtain a white precipitate, which was then centrifuged to obtain a white product, which was then washed and dried to obtain terephthalic acid.

[0046] S2. Weigh 2 g of terephthalic acid obtained in step S1, 1.25 g of copper nitrate trihydrate, 10 mL of N,N-dimethylformamide, 10 mL of ethanol, and 10 mL of deionized water, mix well, transfer to a polytetrafluoroethylene-lined reactor, and place in an oven at 85°C for 24 h.

[0047] S3. After cooling, centrifugal separation, washing and drying were performed to obtain 0.8 g of Cu-MOF material.

[0048] S4. Take 10 mg of the Cu-MOF material, add 1 mL of ethanol and 100 μL of Nafion to make an ink-like slurry, and apply it on carbon paper after ultrasonication to prepare a Cu-MOF electrode material.

[0049] The XRD pattern of the prepared Cu-MOF electrode material is shown in Figure 1 The LSV diagram of the prepared Cu-MOF electrode material is shown in Figure 2As shown. Figure 1 A high-intensity diffraction peak at 9° and a low-intensity diffraction peak at 17.5° can be observed, indicating the successful synthesis of Cu-MOF. Figure 2 The LVS results show that Cu-MOF has a 2 The current response under the atmosphere is higher than that under Ar atmosphere, indicating that Cu-MOF has a strong affinity for CO 2 It has electrocatalytic activity.

[0050] Example 5

[0051] A Cu-MOF electrode material for electrocatalysis of CO 2 The method for preparing formic acid by reduction comprises the following steps:

[0052] The electrochemical workstation was used to test the electrocatalytic performance of the Cu-MOF electrode material in a three-electrode system. 2 Faradaic efficiency of reduction to formic acid, in terms of CO 2 Saturated 0.5M potassium bicarbonate was used as the electrolyte, and the working electrode was a Cu-MOF catalyst supported on carbon paper. The catalyst dosage was 1.4 mg / cm 2 The reference electrode is Ag / AgCl electrode, the counter electrode is platinum sheet, and the liquid phase product is analyzed by nuclear magnetic resonance and the gas phase product is analyzed by gas chromatography. The results are as follows Figure 3 As shown, the formic acid Faradaic efficiency of the Cu-MOF catalyst at a wide voltage range of -1.5 V to -1.7 V (vs. Ag / AgCl) is higher than 33%, and the formic acid Faradaic efficiency at -1.65 V (vs. Ag / AgCl) can reach 53%.

[0053] Example 6

[0054] A Ru-MOF electrode material for electrocatalysis of CO 2 The method for preparing formic acid by reduction comprises the following steps:

[0055] The Ru-MOF electrode material was used to test the electrocatalytic CO 2 Faradaic efficiency of reduction to formic acid, in terms of CO 2 Saturated 0.5M potassium bicarbonate was used as the electrolyte, and the working electrode was a Cu-MOF catalyst supported on carbon paper. The catalyst dosage was 1.4 mg / cm 2 The reference electrode was an Ag / AgCl electrode, the counter electrode was a platinum sheet, and the liquid phase product was analyzed by nuclear magnetic resonance and the gas phase product was analyzed by gas chromatography. The results showed that the formic acid Faradaic efficiency of the Ru-MOF catalyst at a voltage of -1.55V (vs.Ag / AgCl) was 28%.

[0056] Example 7

[0057] A Mn-MOF electrode material for electrocatalysis of CO 2 The method for preparing formic acid by reduction comprises the following steps:

[0058] The electrochemical workstation was used to test the electrocatalytic activity of Mn-MOF electrode materials on CO 2 Faradaic efficiency of reduction to formic acid, in terms of CO 2 Saturated 0.5M potassium bicarbonate was used as the electrolyte, and the working electrode was a Cu-MOF catalyst supported on carbon paper. The catalyst dosage was 1.4 mg / cm 2 The reference electrode was an Ag / AgCl electrode, the counter electrode was a platinum sheet, and the liquid phase product was analyzed by nuclear magnetic resonance and the gas phase product was analyzed by gas chromatography. The results showed that the formic acid Faradaic efficiency of the Ru-MOF catalyst at a voltage of -1.6V (vs.Ag / AgCl) was 12%.

[0059] Example 8

[0060] A Fe-MOF electrode material for electrocatalysis of CO 2 The method for preparing formic acid by reduction comprises the following steps:

[0061] The electrochemical workstation was used to test the electrocatalytic activity of Fe-MOF electrode materials on CO 2 Faradaic efficiency of reduction to formic acid, in terms of CO 2 Saturated 0.5M potassium bicarbonate was used as the electrolyte, and the working electrode was Fe-MOF catalyst supported on carbon paper. The catalyst dosage was 1.4 mg / cm 2 The reference electrode was an Ag / AgCl electrode, the counter electrode was a platinum sheet, and the liquid phase product was analyzed by nuclear magnetic resonance and the gas phase product was analyzed by gas chromatography. The results showed that the formic acid Faraday efficiency of the Fe-MOF catalyst was 10% at a voltage of -1.65V (vs.Ag / AgCl).

Claims

1. A method for preparing MOF-derived electrode materials using PET waste plastics as a source of organic ligands, characterized in that The steps include: S1. Put PET waste plastic or terephthalic acid obtained by depolymerization of PET into a glass beaker, add metal salt, N,N-dimethylformamide, alcohol and deionized water, mix and stir, transfer to a polytetrafluoroethylene-lined reactor, and react at a certain temperature; S2. After cooling, centrifugation, washing and drying are performed to obtain the MOF material; S3. Take MOF material, add ink-like slurry made of Nafion and alcohol, and apply it on carbon paper after ultrasonication to prepare MOF-derived electrode material.

2. The method for preparing a MOF-derived electrode material according to claim 1, characterized in that In step S1, the metal salt is one or more of manganese chloride, manganese nitrate, manganese sulfate, ferrous sulfate, ferrous nitrate, ferrous chloride, ferrous acetylacetonate, ferric sulfate, ferric nitrate, ferric chloride, copper nitrate, copper sulfate, copper chloride, copper bromide, copper acetylacetonate, ruthenium trichloride, ruthenium nitrate and hydrate.

3. The method for preparing a MOF-derived electrode material according to claim 1, characterized in that In step S1, the alcohol is one or more of methanol, ethanol, ethylene glycol, 1,3-propylene glycol, glycerol, 1,4-butanediol, and phenylethyl alcohol.

4. The method for preparing a MOF-derived electrode material according to claim 1, characterized in that In step S1, the molar ratio of the PET waste plastic to the metal salt is 0.5-3:

1.

5. The method for preparing a MOF-derived electrode material according to claim 1, characterized in that In step S1, the volume ratio of N,N-dimethylformamide to alcohol and deionized water is: 1-3:0-3 :

1.

6. The method for preparing a MOF-derived electrode material according to claim 1, characterized in that In step S1, the temperature is 80-180°C and the reaction time is 24-48h.

7. The method for preparing a MOF-derived electrode material according to claim 1, characterized in that In step S3, the solid-liquid ratio of the MOF material to Nafion is 0.1-1:1 g / mL.

8. Use of the MOF-derived electrode material according to claim 1 in electrocatalytic CO2 reduction.

9. A method for preparing formic acid by electrocatalytic reduction of CO2 using the MOF-derived electrode material of claim 1, characterized in that The method comprises the following steps: using an electrochemical workstation, taking the MOF-derived electrode material according to claim 1 as a working electrode, taking an Ag / AgCl electrode as a reference electrode, taking a CO2-saturated metal salt solution as an electrolyte, and electrocatalyzing CO2 reduction to formic acid.

10. The method according to claim 9, characterized in that The metal salt is one or more of potassium bicarbonate, potassium chloride, potassium sulfate, sodium sulfate, sodium bicarbonate, cesium bicarbonate, and cesium sulfate; the electrolyte concentration is 0.1-1.2 mol / L; the amount of MOF-derived electrode material loaded on carbon paper is 0.5-2.5 mg / cm 2 , the counter electrode is a platinum sheet.

Citation Information

Patent Citations

  • Sulfur-modified Cu-based MOF material, preparation method and application of sulfur-modified Cu-based MOF material in electrocatalytic CO2 reduction reaction

    CN112301375A

  • A Cu-MOF material for electrocatalytic reduction of CO2 and its preparation method

    CN113355688B

Cited By

  • Waste PET (polyethylene terephthalate)-based MOFs (metal organic frameworks) functional material as well as preparation method and application thereof

    CN121226755A